THE ANALYSIS OF THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE IN IMPROVING COMPANY PERFORMANCE AT SUB-HOLDING PT. PELINDO MULTI TERMINAL - Aulia Fitri Ramadhani; Sahnan Rangkuti; Suardi Suardi (Bisnis-Net, 2023)
Good business governance (GCG) is essential for the sustainability and development of a company in the future. The principles of implementing GCG, which include transparency, accountability, responsibility, independence, and fairness, are fundamental in managing business, especially in state-owned companies as regulated in the Minister of State for State-Owned Enterprises Regulation Number: PER – 01 / MBU/2011 concerning the Implementation of Governance Good Company (Good Corporate governance).PT. Pelindo Multi Terminal is a sub-holding company of PT Pelabuhan Indonesia (Persero), which manages port business entities in multipurpose terminal operations in Indonesia. The implementation of good corporate governance in the company has not been optimal due to a lack of socialization to communicate, educate, and convey information about GCG to employees by position holders.This research uses qualitative research methods with informants from relevant positions, company employees and service users. The research results show a lack of socialization from office holders so that new employees do not understand GCG, the principles of accountability, starting from the delivery of information and financial reports, have not been carried out promptly, and the principles of responsibility in service sessions have not been maximized, indicated by, among other things, limited internet access and providing comfort and satisfaction to customers.